The Anthropological Approach to Education and Modern Training and Learning Methodology - Holubnycha, Liudmyla; Shchokina, Tetiana; Soroka, Natalia (Educational Challenges, 2023)
The paper deals with the anthropological approach to education in particular to teaching theory through the prism of the correlation between the mentioned approach and modern teaching and learning methodology. The purpose is to establish and trace the correlation between anthropological approach to education and modern teaching and learning methodology The tasks are: to find out the essence of the anthropology in relation to pedagogy; to reveal and describe teaching and learning models based on anthropological approach to teaching theory; to figure out effective instruction methods, which can be applied within the designated teaching and learning models. The methods of the investigation are analysis and syntheses of the related scientific materials aimed at collecting and presenting the results as well as drawing the conclusion. The results revealed three different understandings of the essence of the studied phenomenon, one of which (as a methodological core and a modern paradigm of the complex of pedagogical sciences with practical orientation of education to the person as its main goal and value) is associated with our investigation. Among the correspondent teaching and learning models we revealed and described personality-oriented learning model, student-centered learning model and a model based on individual approach to teaching. A number of effective instruction methods (as: problem-based learning, case study, inquiry-based learning, discovery-based learning, role playing game, game learning, different forms of dialogic learning, team learning and others) was figured out. The conclusion is that in modern educational system anthropological approach is one of the central as knowledge about human, his nature and the laws of his development allows designing the educational process.